Tiering Style and Its Interpretation: Ichnofabric Study in Balikpapan Formation, Kutai Basin, Indonesia - Ery Arifullah; Yahdi Zaim; Aswan Aswan; Djuhaeni Djuhaeni (Institute for Research and Community Services (LPPM) ITB, 2019)
The determination of tiering style is an important task in ichnology. Tiering styles can be modeled by using ichnodiversity, the number of behaviors and number of tiers and their relationships. In this study, this approach was applied in the area of Samarinda, Kutai Basin, Indonesia. The values of ichnodiversity, number of behaviors, and number of tiers were identified. Ichnodiversity was strongly correlated with number of behaviors but weakly correlated with number of tiers. Accordingly, three tiering styles were identified. Typically, tiering styles A, B, and C demonstrated high ichnodiversity, number of behaviors and number of tiers. In general, the colonization window that coincides with the environmental conditions characteristic for deltaic settings is the factor that mostly regulates these tiering styles.